(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
To analyze the effectiveness of laser photocoagulation in preventing complications of diabetic retinopathy (DR) in patients without clinical symptoms and to evaluate its role in early intervention.